Synthesis and characterization of gefitinib and paclitaxel mono and dual drug-loaded blood cockle shells (Anadara granosa)-derived aragonite CaCO3 nanoparticles - Chemmalar, S.; Abdul Razak, Intan Shameha; Che Abdullah, Che Azurahanim; Ab Razak, Nor Asma; Mohamad Yusof, Loqman; Ajat, Mokrish; Gowthaman, N. S. K.; Abu Bakar, Md Zuki (MDPI AG, 2021)
Calcium carbonate has slowly paved its way into the field of nanomaterial research due to its inherent properties: biocompatibility, pH-sensitivity, and slow biodegradability. In our efforts to synthesize calcium carbonate nanoparticles (CSCaCO3NP) from blood cockle shells (Anadara granosa), we developed a simple method to synthesize CSCaCO3NP, and loaded them with gefitinib (GEF) and paclitaxel (PTXL) to produce mono drug-loaded GEF-CSCaCO3NP, PTXL-CSCaCO3NP, and dual drug-loaded GEF-PTXL-CSCaCO3NP without usage of toxic chemicals. Fourier-transform infrared spectroscopy (FTIR) results reveal that the drugs are bound to CSCaCO3NP. Scanning electron microscopy studies reveal that the CSCaCO3NP, GEF-CSCaCO3NP, PTXL-CSCaCO3NP, and GEF-PTXL-CSCaCO3NP are almost spherical nanoparticles, with a diameter of 63.9 ± 22.3, 83.9 ± 28.2, 78.2 ± 26.4, and 87.2 ± 26.7 (nm), respectively. Dynamic light scattering (DLS) and N2 adsorption-desorption experiments revealed that the synthesized nanoparticles are negatively charged and mesoporous, with surface areas ranging from ~8 to 10 (m2/g). Powder X-ray diffraction (PXRD) confirms that the synthesized nanoparticles are aragonite. The CSCaCO3NP show excellent alkalinization property in plasma simulating conditions and greater solubility in a moderately acidic pH medium. The release of drugs from the nanoparticles showed zero order kinetics with a slow and sustained release. Therefore, the physico-chemical characteristics and in vitro findings suggest that the drug loaded CSCaCO3NP represent a promising drug delivery system to deliver GEF and PTXL against breast cancer.